2x2 + 5x = x*(2x + 5)
Let square = [x] -4+3*(-2)*[-4]+[3x-2x]=-4-6-2+[x]=-12+[x]The answer is negative 12 plus squared x.
17
no posible answerImproved Answer:-2x2+x-3 = (2x+3(x-1) when factored
((15xy2)/(x2+5x+6))/((5x2y)/(2x2+7x+3)) =(15xy2/5x2y)*(2x2+7x+3)/(x2+5x+6) =(3y/x)*(((2x+1)(x+3))/((x+2)(x+3) =(3y(2x+1))/(x(x+2)) =(6xy+3y)/(x2+2x)
4
Add the x's squared together to get 2x^2+x. You cannot add anymore so the answer is 2x^2+x
2x2 + 2x = 2x(x+1)
x(x + 2)
4
x^2+x^2=2x^2
2x(x^2+x-6)
(x - 1)(2x^2-1)
(2x+3)(x+3)
(x + 1)(2x + 5)
(2x + 1)(x + 2)
(2x+10)(x+4)